Neurotrophin-3 released from implant of tissue-engineered fibroin scaffolds inhibits inflammation, enhances nerve fiber regeneration, and improves motor function in canine spinal cord injury - Li G. (John Wiley and Sons Inc., 2019)
10.1002/jbm.a.36414